Real-Time Robust Simultaneous Catheter and Environment Modeling for Endovascular Navigation - Zhao,L; Giannarou,S; Lee,SL; Yang,GZ (2020)
Due to the complexity in catheter control and navigation, endovascular procedures are characterized by significant challenges. Real-time recovery of the 3D structure of the vasculature intraoperatively is necessary to visualize the interaction between the catheter and its surrounding environment to facilitate catheter manipulations. Nonionizing imaging techniques such as intravascular ultrasound (IVUS) are increasingly used in vessel reconstruction approaches. To enable accurate recovery of vessel structures, this chapter presents a robust and real-time simultaneous catheter and environment modeling method for endovascular navigation based on IVUS imaging, electromagnetic (EM) sensing as well as the vessel structure information obtained from the preoperative CT/MR imaging. By considering the uncertainty in both the IVUS contour and the EM pose in the proposed nonlinear optimization problem, the proposed algorithm can provide accurate vessel reconstruction, at the same time deal with sensing errors and abrupt catheter motions. Experimental results using two different phantoms, with different catheter motions demonstrated the accuracy of the vessel reconstruction and the potential clinical value of the proposed vessel reconstruction method.